2003
DOI: 10.1677/jme.0.0300001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of oestradiol, tamoxifen and raloxifene on nerve growth factor-alpha expression in specific neonatal mouse uterine cell types using laser capture microdissection

Abstract: Oral dosing of CD-1 mice on days 2-5 after birth with tamoxifen but not raloxifene disrupts the development of the myometrium, resulting in adult uterine adenomyosis. Using laser capture microdissection and RT-PCR we have investigated nerve growth factor (NGF) and cognate receptor expression in uterine cells of 6-day-old pups that may be important in early developmental changes that give rise to adenomyosis. NGF down-regulation is known to occur during terminal myogenic differentiation.NGF was found exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…Tamoxifen, but not estradiol neonatal exposure, resulted in the development of adenomyosis in CD1 mice as early as day 10, with the disruption of the inner myometrial layer and ingrowth of endometrial glands and stroma. The doses of tamoxifen and estradiol used in our work were derived from the dose-response studies , and have been previously described and utilized in the similar experiments , Green et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen, but not estradiol neonatal exposure, resulted in the development of adenomyosis in CD1 mice as early as day 10, with the disruption of the inner myometrial layer and ingrowth of endometrial glands and stroma. The doses of tamoxifen and estradiol used in our work were derived from the dose-response studies , and have been previously described and utilized in the similar experiments , Green et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…LCM allows the isolation of specific uterine cell types without contamination from other cell types. Green et al (2003) showed that mRNA from cells could be successfully isolated by LCM from frozen sections with high efficiency, producing RNA with excellent quality and quantity. We isolated populations of specific uterine cell types from frozen sections stained with Mayer's hematoxylin: luminal epithelial, stromal and muscle cells.…”
Section: Analysis Of Selected Gene Expression Patterns In Specific Utmentioning
confidence: 99%
“…We also employed a combination of laser capture microdissection (LCM) and RT-PCR to quantify estrogen-responsive genes in specific cell types of the ovariectomized mouse uterus. Recently, LCM has been used to isolate specific cell types from tissue sections for the purpose of differential gene expression (Green et al 2003). Using these techniques, we profiled both early and late responsive genes regulated by estrogen and demonstrated that several responsive genes were differentially expressed in specific cell types of the estrogen-induced uterus.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggest that estrogen can alter the expression of neurotrophin receptors and perhaps even neurotrophins (16,17,35). We first demonstrated that estrogen enhances the expression of p75NTR in 22Rv1 prostate cancer cells, This effect occurs in association with the up-regulated expression of ESR2, suggesting that estrogen might not only directly regulate p75NTR expression, but may also influence the neurotrophin pathways via their receptors.…”
Section: Discussionmentioning
confidence: 88%
“…Estrogen receptors are co-localized in cells that express neurotrophins and their receptors, and estrogen further regulates the expression of the neurotrophic system in many tissues, not just the nervous system (14,15). Estrogen treatment can induce the expression of p75NTR in Estrogen in combination with 5-azacitidine up-regulates p75NTR expression and induces apoptosis in 22Rv1 prostate cancer cells uterine cells and in cholinergic neurons (16,17), but little is known regarding its effects in the prostate. We speculated that interactions between estrogen and the neurotrophic system may partially explain the beneficial effects of estrogen therapy for androgen-refractory prostate cancer.…”
Section: Introductionmentioning
confidence: 99%